Geological heritage in the Alto Ribeira State and Touristic Park (São Paulo State, Brazil): Inventory and quantification of geosites - Rodrigues Ferreira, Ana Rita; Santos Lobo, Heros Augusto; Jesus Perinotto, José Alexandre (My University, 2013)
The geological and geomorphological context of The Alto Ribeira State and Touristic Park (PETAR) associated to its great landscape aesthetical value makes the one of most important speleological regions in Brazil. More than 400 caves have been registered (CNC/SBE) with a wide variety of speleothem forms, as well a variety of waterfalls, trails and traditional communities can be found within the Park. The region has a high potential for development of geotourism, therefore a geoconservation strategy should be outlined. The Geological heritage inventory and quantification are the first step to perform a geoconservation strategy, that also includes the classification, conservation, promotion and monitoring of geosites. The proposed methodology for inventory and quantification is based on a range of criteria that covers its scientific, didatic and touristic significance, and is being performed and tested in PETAR. © Società Geologica Italiana, Roma 2013.
Keywords: Assessment; Geoconservation; Geoheritage; Geosites; Geotourism